2018
DOI: 10.7196/samj.2018.v108i7.12543
|View full text |Cite
|
Sign up to set email alerts
|

Quality of counselling and support provided by the South African National AIDS Helpline: Content analysis of mystery client interviews

Abstract: Background. Telephone helplines can facilitate referral, education and support for patients living with HIV or those concerned about the infection. The anonymity of helplines facilitates discussion of sensitive issues that are difficult to raise face to face. These services could support the expansion of HIV self-testing. However, maintaining quality and standardising messages in rapidly evolving fields such as HIV is challenging. Objectives. To evaluate the quality of the South African (SA) National AIDS Help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Arullapan et al [ 2 ] conducted a cross sectional study of telephone calls from ‘mystery clients’ to a HIV helpline. In their study 83% of all calls were deemed to be empathetic by the ‘mystery client’ researcher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arullapan et al [ 2 ] conducted a cross sectional study of telephone calls from ‘mystery clients’ to a HIV helpline. In their study 83% of all calls were deemed to be empathetic by the ‘mystery client’ researcher.…”
Section: Resultsmentioning
confidence: 99%
“…This is reflected in the majority of studies where patient experiences were addressed [ [2] , [4] , [32] , 7 , 24 , 35 ]. All of these studies suggested that patients rated their teleconsultations as being empathic.…”
Section: Summary Of Reporting Biasesmentioning
confidence: 99%